There's nothing as practical as understanding the nature of theory: A phenomenographic study of management educators' implicit theories of theory. Issue 2 (April 2023) - Eichler, Michael; Billsberry, Jon
Although teaching in Business Schools takes a theory-driven perspective, there are multiple different interpretations of what this means. We make a contribution by examining how management educators define 'theory' and explore how differing definitions lead to variations in the way that teaching is conceptualised and designed. We adopt phenomenographic methods to reveal a five-level hierarchy of theory definitions ranging from simple descriptive notions of 'theory as an idea' to more explanatory definitions with causal and practice implications. This hierarchy shapes the way management educators design their teaching with those with the most sophisticated understanding of theory being the most practically focused in their teaching. Although all the interviewees view theory as having an interventional purpose to shape or change managerial action, management educators are haphazard in the ways they teach students to apply theory. We conclude by discussing the implications of these findings for the essential–non-essentialist debate in management education and suggest avenues for future research.